SPE Asia Pacific Oil and Gas Conference and Exhibition 2008
DOI: 10.2118/116424-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Storage—Managing the Risk Associated With Well Leakage over Long Timescales

Abstract: One of the major challenges associated with CO2 geological storage is the performance of the confining system over long timescales. In particular, the occurrence of CO2 leakage through existing wells could not only defeat the purpose of storage but also badly affect human health or the environment. Indeed, cement degradation and casing corrosion in injection, production or abandoned wells can create preferential channels over time, allowing migration of CO2 from the reservoir to shallower formations (e.g. aqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The interaction between cement and CO 2 in the rocks has gained significance in recent years Moroni et al 2009;Brandl et al 2010;Le Guen et al 2008). Geological storage of CO 2 in depleted and partially depleted oil fields has gained increasing global interest as an economically viable means of reducing CO 2 emissions, while recovering extra oil.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between cement and CO 2 in the rocks has gained significance in recent years Moroni et al 2009;Brandl et al 2010;Le Guen et al 2008). Geological storage of CO 2 in depleted and partially depleted oil fields has gained increasing global interest as an economically viable means of reducing CO 2 emissions, while recovering extra oil.…”
Section: Introductionmentioning
confidence: 99%
“…3.4.16) and the mass of CO 2 leakage to the secondary reservoir was also reduced. Risk mitigation measures of additional well characterisation (Le Guen et al, 2008) are suggested and included as part of the preventative measures plan (Hannis et al, 2013c;Shi et al, 2013) and 'dry-run' storage permit application for the site (Hannis et al, 2013a). Baseline observation and resurvey of the sea bed during injection over existing well sites by sonar and echo sounder surveys (Shi et al, 2013) are a component of the monitoring plan (Hannis et al, 2013c).…”
Section: Risk: Fluid Escape Pathways Up Abandoned Wellsmentioning
confidence: 99%
“…The interaction between cement and CO 2 in the formation has been an area of interest in recent years Moroni et al 2009;Brandl et al 2010;Le Guen et al 2008). When cement hydrates, the major products formed during the hydration reaction are calcium hydroxide (portlandite), calciumsilicate-hydrate (C-S-H), ettringite, and monosulfate.…”
Section: Introductionmentioning
confidence: 99%